Patterns of Left Ventricular Hypertrophy and Late Gadolinium Enhancement onCardiac Magnetic Resonanace in Patients with Hypertrophic Cardiomyopathy - Mehreen, Sobia; Ahmed, Adeel; Sidiqqui, Abdul Hameed; Maken, Ghulam Rasool; Jokhio, Abdul Rehman; Shiram, Syed Ali; Kamran, Javeria; Saeed, Nazish; ., Waqar; Khan, Ismail Ahmed (Pakistan Armed Forces Medical Journal, 2022)
Objective: To evaluate the patterns of left ventricular hypertrophy (LVH) and late gadolinium enhancement (LGE) inhypertrophic cardiomyopathy.Study Design: Analytical cross-Sectional Study.Place and Duration of Study: Tertiary Cardiac Care Center, Rawalpindi Pakistan from 01 June 2020 to 30 Dec 2021.Methodology: This study was carried out at a tertiary cardiac care center retrospectively from 1 June 2020 to 31 December 2021. Patients having LV hypertrophy due to aortic stenosis, hypertension, athlete’s heart, and infiltrative disorders were excluded from study. Cases were included using nonprobability consecutive sampling. Sample size estimated by taking 0.2- 0.5 % (1 in 200-500) prevalence of hypertrophic cardiomyopathy using open epi sample size calculator was (n=38) taking 99.99% confidence interval. For the purpose of study all patients with confirmed HCM undergoing CMR during given period were included in study.Approval from the ethical review committee with IERB (IERB letter # 9/2/R&D/2022/179) was sought. CMR was performed using MRI 3 Tesla. Data analysis was done on SPSS version-26. Quantitative variables were expressed as Mean±SD. Qualitative variables were expressed as frequencies and percentages. ANOVA and student t-test (95% CI and 5% margin of error) was applied to compare the study variables. p-vale